1983
DOI: 10.1210/endo-113-5-1551
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Inhibits Basal and Vasoactive Intestinal Peptide-Stimulated Hormone Release by Different Mechanisms in GH Pituitary Cells*

Abstract: Somatostatin (SRIF) inhibits both basal and vasoactive intestinal peptide (VIP)-stimulated hormone secretion by the GH4C1 clonal strain of rat pituitary tumor cells. We have previously shown that SRIF inhibits cAMP accumulation stimulated by VIP but does not alter basal cAMP levels in this cell line. To determine the importance of changes in cAMP accumulation in the mechanism of SRIF action, we have compared the effect of SRIF on hormone release stimulated by VIP and two other secretagogues which increase effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

1985
1985
1997
1997

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 35 publications
(55 reference statements)
1
32
1
Order By: Relevance
“…Therefore, the present results in rat prostatic epithelial cells suggest the existence of somatostatin receptors coupled to adenylate cyclase in an inhibitory manner, probably through a guanosine nucleotide-binding protein [13]. However, further studies are required to understand the precise role of cyclic AMP in the action of somatostatin at this level since a cyclic AMPindependent mechanism may also be involved in some somatostatin effects in various tissues [7]. Finally, the exact nature of somatostatin receptors in prostatic epithelium remains to be established since biologically active somatostatin receptors appear to exist in both plasma membrane and intracellularly in various systems [14].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Therefore, the present results in rat prostatic epithelial cells suggest the existence of somatostatin receptors coupled to adenylate cyclase in an inhibitory manner, probably through a guanosine nucleotide-binding protein [13]. However, further studies are required to understand the precise role of cyclic AMP in the action of somatostatin at this level since a cyclic AMPindependent mechanism may also be involved in some somatostatin effects in various tissues [7]. Finally, the exact nature of somatostatin receptors in prostatic epithelium remains to be established since biologically active somatostatin receptors appear to exist in both plasma membrane and intracellularly in various systems [14].…”
Section: Discussionmentioning
confidence: 74%
“…Somatostatin is a well known inhibitor of cyclic AMP synthesis stimulated by a number of agents including VIP [7] and catecholamines [8] in other tissues. The present study examined the action of somatostatin, both alone or in combination with VIP and the /Y-adrenergic agonist isoproterenol, upon cyclic AMP accumulation in isolated epithelial cells of rat ventral prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Although both possess a similar affinity for somatostatin-14 and -28, their sequences are surprisingly divergent. This sequence divergence may well underlie the diverse biological effects of somatostatin (2) by coupling its receptors to different intracellular effector systems (27,28). The cloning of SSTR1 and SSTR2 should lead to a better understanding of the molecular basis for SSTR heterogeneity as determined by cross-linking analyses (29)(30)(31)(32) and the mechanisms and regulation of somatostatin function.…”
Section: Methodsmentioning
confidence: 99%
“…GHRH and VIP are known to exert their actions through the activation of CAMP [2,21], whereas SRIF may exert its effects on GH secretion by interfering with cAMP production or by an action on the secretory process subsequent to CAMP production in rats [23]. It has also been reported that VIP directly stimulates somatotrophs and that the effect seems to imply a coupling of VIP receptors with cAMP production in rats [6], and the SRIF-induced inhibition of VIP-stimulated GH release from rat pituitary tumor cells is closely coupled to the inhibition of VIP-stimulated CAMP accumulation [27]. Since amino acid sequences are considerably overlapped between VIP and GHRH [1], VIP may exhibit 'GRF-like' activity under physiological condition [11].…”
Section: Discussionmentioning
confidence: 97%